PENINGKATAN RENDEMEN BARECORE DI PT ANUGERAH TRISTAR INTERNASIONAL - Michael Raymond; Felecia - (Jurnal Titra, 2014)
PT Anugerah Tristar Internasional is a woodworking company which produces barecore. Barecore is a wooden board that made from small pieces of wood that glued together, barecore is used for the central part of the plywood. The company’s current problem is that the average yield rate only 46.24%. From the current condition there are few problems. One of them is variability in the raw material size and quality. Another problem is the high rate of waste produced up to 53.76% and this waste is never recycled. The proposed improvement is to re-use the waste to produce new barecore. This will require extra processing and sorting of the waste. The improvement increase the average yield rate up to 5.72% for the company and profit Rp. 3.053.500,00/m3 barecore.